KRISTALISASI AMMONIUM PERKLORAT (AP) DENGAN SISTEM PENDINGINAN TERKONTROL UNTUK MENGHASILKAN KRISTAL BERBENTUK BULAT - Pinalia, Anita (Indonesian Journal of Aerospace, 2011)
AP is the solid particles with the largest composition in compossite propellant, with fractions 60-80%. Rounded particles of AP indirectly gives better performance of propellant. Therefore we need experiment the crystallization process to produce rounded AP crystal. In this experiment, crystallization was conducted by using a controlled cooling system. Cooling is done through two stages and using a different coolant. The first stage of slow cooling using water (30°C), and continued rapid cooling with ethylene glycol (-27°C). These experiment generate 45.45 kg AP with a purity 99.67%, 40 mesh crystal size, crystal shape close to round, yield 39.71%.